A crystal growth kinetics guided Cu aerogel for highly efficient CO2 electrolysis to C2+ alcohols. Issue 2 (12th December 2022) - Li, Pengsong; Bi, Jiahui; Liu, Jiyuan; Zhu, Qinggong; Chen, Chunjun; Sun, Xiaofu; Zhang, Jianling; Liu, Zhimin; Han, Buxing
Abstract : Controlling crystal growth kinetics using different reductants is an efficient strategy to modulate the surficial chemistry micro-circumstance of Cu aerogels, enabling the creation of efficient surface sites for increasing C2+ product selectivity. Abstract : To realize commercial CO2 electrochemical reduction to C2+ alcohols, the selectivity and production rate should be further improved. Establishing controllable surface sites with a favorable local environment is an interesting route to guide the C2+ pathway. Herein, we report a room-temperature one-step synthetic strategy to fabricate a highly stable Cu aerogel as an efficient CO2 reduction electrocatalyst. Controlling crystal growth kinetics using different reductants is an efficient strategy to modulate the nucleation and growth rate of Cu aerogels, enabling the creation of efficient surface sites for the C2+ pathway. Over the Cu aerogel obtained by reducing Cu 2+ using a weak reductant (NH3 ·BH3 ), the faradaic efficiency of C2+ products could reach 85.8% with the current density of 800 mA cm −2 at the potential of −0.91 V vs. reversible hydrogen electrode, and the C2+ alcohol selectivity was 49.7% with a partial current density of 397.6 mA cm −2, while the Cu aerogel prepared using a strong reductant (NaBH4 ) was favorable to generating CO. Experimental and theoretical studies showed that the selectivity of the reaction depended strongly on the desorption and dimerization of *CO intermediates on the catalysts. The strong reductant induced a defective Cu surface that could facilitate the desorption of the *CO intermediate, subsequently producing CO, whereas the low defect Cu produced using a weak reductant could significantly enhance the selectivity for the C2+ product by improving *CO adsorption and the C–C coupling on the catalyst. This work opens a new way for constructing efficient electrocatalysts for CO2 electroreduction to C2+ alcohols.